2014
DOI: 10.4102/hts.v70i3.2060
|View full text |Cite
|
Sign up to set email alerts
|

The effect of misapplied religious practices in some alternative religious groups

Abstract: The positive impact that religion generally has on human beings has been suggested by different studies. However, it cannot be assumed that religion always contributes to the wellbeing of believers. Religious systems can be misused, resulting in people being spiritually and even physically hurt and harmed. This study investigates certain aspects of some alternative religious group in order to determine the impact it has on the well-being of the members of these groups. It was found that people are drawn to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It could be related to the influences of participants' current involvement with NRS. For example, research has indicated difficulty in functioning well in society after leaving certain new religious movement groups (Pretorius, 2014), and many of these groups emphasize spirituality over religion (Clarke, 2006). More research on how NRS or involvement with new religious movement groups is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It could be related to the influences of participants' current involvement with NRS. For example, research has indicated difficulty in functioning well in society after leaving certain new religious movement groups (Pretorius, 2014), and many of these groups emphasize spirituality over religion (Clarke, 2006). More research on how NRS or involvement with new religious movement groups is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Nonreligious Spirituality (NRS) has been attracting more attention from psychological research in recent years (Aird et al, 2010; Buxant et al, 2007; Coates, 2012; Davis et al, 2015; Houtman et al, 2009; Pretorius, 2014). Much of this research has yielded positive results.…”
Section: Mental Health Symptomsmentioning
confidence: 99%
See 2 more Smart Citations